An interpretative phenomenological analysis of dignity in people with multiple sclerosis - Žiaková, Katarína; Čáp, Juraj; Miertová, Michaela; Gurková, Elena; Kurucová, Radka (Nursing ethics, 2020)
BACKGROUND: Dignity is a fundamental concept in healthcare. The symptoms of multiple sclerosis have a negative effect on dignity. Understanding of lived experience of dignity in people with multiple sclerosis is crucial to support dignity in practice. RESEARCH AIM: The aim was to explore the sense of dignity experienced by people with multiple sclerosis. RESEARCH DESIGN AND PARTICIPANTS: An interpretative phenomenological analysis design was adopted, using data collected through face-to-face interviews with 14 participants. ETHICAL CONSIDERATIONS: The study was approved by the faculty Ethical Committee (No. EC 1828/2016). FINDINGS: Four interconnected superordinate themes emerged from analysis: Loss of a fully-fledged life: Violating the dignity-of-self; To accept and fight: Promoting the dignity-of-self; Contempt and rudeness: Indignity-in-relation; and Those who know and see, help: Promoting dignity-in-relation. The loss of former fully-fledged life has a dramatic impact on integrity and impaired dignity-of-self. Accepting illness and changed identity impaired by multiple sclerosis was the step that the participants considered to be important for reacquiring the sense of dignity. The participants encountered misunderstandings, prejudices, embarrassment, insensitive remarks, labelling, unwillingness and impersonal treatment as indignities. Acceptance of their condition, needed support, the feeling of being part of a group, sensitivity and the sharing of problems had a positive effect on their dignity. DISCUSSION: Continual changes in functional ability threaten an individual's identity and were experienced as violations of dignity. Based on this, participant's dignity-of-self was not a moral, but much more existential value. Acceptance of changed identity and fighting spirit were important for restoring their dignity-of-self. The misunderstandings, prejudices and unwillingness had a negative impact on their dignity-in-relation. On the other side, support from others in fighting promoted their dignity-in-relation. CONCLUSION: Dignity is manifested as a complex phenomenon of lived experience of people with multiple sclerosis and also an umbrella concept for providing good quality of person-centred care.
Keywords: rozhovory jako téma; dospělí; Qualitative Research; důstojnost lidského života; Female; Interviews as Topic; Adult; ženské pohlaví; lidé; Multiple Sclerosis; Personhood; roztroušená skleróza; uznání; Male; lidé středního věku; mužské pohlaví; Middle Aged; Respect; kvalitativní výzkum; Humans